Short‐term high‐fat diet primes excitatory synapses for long‐term depression in orexin neurons. (18th December 2017) - Linehan, Victoria; Fang, Lisa Z.; Hirasawa, Michiru
Abstract : Key points: High‐fat diet consumption is a major cause of obesity. Orexin neurons are known to be activated by a high‐fat diet and in turn promote further consumption of a high‐fat diet. Our study shows that excitatory synapses to orexin neurons become amenable to long‐term depression (LTD) after 1 week of high‐fat diet feeding. However, this effect reverses after 4 weeks of a high‐fat diet. This LTD may be a homeostatic response to a high‐fat diet to curb the activity of orexin neurons and hence caloric consumption. Adaptation seen after prolonged high‐fat diet intake may contribute to the development of obesity. Abstract: Overconsumption of high‐fat diets is one of the strongest contributing factors to the rise of obesity rates. Orexin neurons are known to be activated by a palatable high‐fat diet and mediate the activation of the mesolimbic reward pathway, resulting in further food intake. While short‐term exposure to a high‐fat diet is known to induce synaptic plasticity within the mesolimbic pathway, it is unknown if such changes occur in orexin neurons. To investigate this, 3‐week‐old male rats were fed a palatable high‐fat western diet (WD) or control chow for 1 week and then in vitro patch clamp recording was performed. In the WD condition, an activity‐dependent long‐term depression (LTD) of excitatory synapses was observed in orexin neurons, but not in chow controls. This LTD was presynaptic and depended on postsynaptic metabotropic glutamate receptor 5 (mGluR5) and retrograde endocannabinoid signalling. WD also increased extracellular glutamate levels, suggesting that glutamate spillover and subsequent activation of perisynaptic mGluR5 may occur more readily in the WD condition. In support of this, pharmacological inhibition of glutamate uptake was sufficient to prime chow control synapses to undergo a presynaptic LTD. Interestingly, these WD effects are transient, as extracellular glutamate levels were similar to controls and LTD was no longer observed in orexin neurons after 4 weeks of WD. In summary, excitatory synapses to orexin neurons become amenable to LTD under a palatable high‐fat diet, which may represent a homeostatic mechanism to prevent overactivation of these neurons and to curtail high‐fat diet consumption. Key points: High‐fat diet consumption is a major cause of obesity. Orexin neurons are known to be activated by a high‐fat diet and in turn promote further consumption of a high‐fat diet. Our study shows that excitatory synapses to orexin neurons become amenable to long‐term depression (LTD) after 1 week of high‐fat diet feeding. However, this effect reverses after 4 weeks of a high‐fat diet. This LTD may be a homeostatic response to a high‐fat diet to curb the activity of orexin neurons and hence caloric consumption. Adaptation seen after prolonged high‐fat diet intake may contribute to the development of obesity.